PERLINDUNGAN HUKUM KONSUMEN KREDIT DALAM SKEMA PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG DI INDONESIA - Juli Sautman Simbolon; Achmad Fitrian; Gatut Hendro Tri Widodo (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study is motivated by the legal position of credit consumers within the mechanism of Suspension of Debt Payment Obligations (PKPU), which normatively treats them identically to other debtors or creditors without specific recognition of their potentially vulnerable economic and structural position. As a collective legal mechanism, PKPU primarily emphasizes procedural certainty and efficiency in debt settlement, often subordinating the individual interests of credit consumers, particularly when they are classified as concurrent creditors who bear the greatest financial risk. This research employs a normative legal research method using statutory, conceptual, and case approaches. The analysis is based on primary legal materials, namely Law Number 37 of 2004 concerning Bankruptcy and PKPU, supported by secondary legal materials such as legal doctrines and scholarly literature on bankruptcy law, as well as tertiary legal materials. The data were analyzed qualitatively to examine the normative construction of PKPU and its implications for the legal protection of credit consumers. The findings indicate that the legal position of credit consumers in PKPU has not been adequately protected due to the absence of affirmative legal norms that distinguish them from other creditors. Existing legal protections, both preventive and repressive, remain largely procedural, formalistic, and reactive, thereby failing to ensure substantive justice for credit consumers. Accordingly, this study highlights the necessity of reforming PKPU regulations to incorporate specific legal protections for credit consumers in order to achieve a balanced integration of legal certainty and substantive justice